2012
DOI: 10.1016/j.bbagrm.2012.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of transcription initiation by the yeast mitochondrial RNA polymerase

Abstract: Mitochondria are the major supplier of cellular energy in the form of ATP. Defects in normal ATP production due to dysfunctions in mitochondrial gene expression are responsible for many mitochondrial and aging related disorders. Mitochondria carry their own DNA genome which is transcribed by relatively simple transcriptional machinery consisting of the mitochondrial RNAP (mtRNAP) and one or more transcription factors. The mtRNAPs are remarkably similar in sequence and structure to single-subunit bacteriophage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 99 publications
1
42
0
Order By: Relevance
“…However, the mechanism by which the chromatin structure in the nucleus affects the expression of genes carried by mitochondrial DNA is less obvious. A major mechanism that regulates the activity of the mitochondrial RNA polymerase Rpo41p/ Mtf1p in vitro is the concentration of ATP (70,71). To test whether this mechanism regulates the transcription of COX1, COX2, and COX3, three genes carried by mitochondrial DNA, we measured the corresponding transcript levels in spt10⌬ cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mechanism by which the chromatin structure in the nucleus affects the expression of genes carried by mitochondrial DNA is less obvious. A major mechanism that regulates the activity of the mitochondrial RNA polymerase Rpo41p/ Mtf1p in vitro is the concentration of ATP (70,71). To test whether this mechanism regulates the transcription of COX1, COX2, and COX3, three genes carried by mitochondrial DNA, we measured the corresponding transcript levels in spt10⌬ cells.…”
Section: Resultsmentioning
confidence: 99%
“…However, how does a defect in the chromatin structure of nuclear genes affect the expression of genes carried by mitochondrial DNA? In vitro, the transcription of genes carried by mitochondrial DNA is regulated by the ATP concentration, and different genes carried by mitochondrial DNA differ in their responsiveness to the ATP level (70,71). However, our results indicate that the increased expression of genes carried by mitochondrial DNA (COX1, COX2, and COX3) in spt10⌬ cells requires the nuclear factors Hap4p and Rtg1p and is driven by the increased expression of the RPO41 and MTF1 genes, encoding mitochondrial RNA polymerase and its associated factor, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The mitochondrial RNA polymerase is of the viral T7 type (reviewed in ref. 22), it is a multidomain polypeptide that contains two to several PPR domains, depending on the organism, located in an N-terminal extension of non-viral origin. The structure of the human mitochondrial RNA polymerase (mtRNAP or POLRMT) has been determined and this is the first crystal structure of a PPR protein.…”
Section: Principal Steps Of Mitochondrial Gene Expression Affected Bymentioning
confidence: 99%
“…In T7 phage, the single-subunit T7 RNAP recognizes the consensus −17 to +6 promoter sequence without requiring any transcription factors. In yeast ( Saccharomyces cerevisiae ) mitochondria, transcription is carried out by a single-subunit class of enzymes related to T7 RNAP, but the core Rpo41 polymerase requires the transcription factor Mtf1 for specific transcription [17]. T7 RNAP discriminates against the non-promoter sequences at the initial binding step, showing ∼10 5 -fold tighter affinity for promoter relative to non-promoter sequences [18].…”
Section: 2 Promoter Bindingmentioning
confidence: 99%
“…Single-molecule time traces showed that Rpo41 alone can bend the promoter DNA to the same degree as Rpo41–Mtf1, however, with a very low frequency. Thus, the low E FRET of the Rpo41-promoter complex observed in ensemble studies is not due to a small bending angle, but a consequence of the rare bending events [49, 17]. The single-molecule FRET time traces measured the DNA bending rates; k bending by Rpo41 alone is 0.0052 s −1 and by Rpo41–Mtf1 is 2.8 s −1 .…”
Section: 3 Promoter Bendingmentioning
confidence: 99%